La recepción de India en América Latina: el caso de Ricardo Güiraldes en la Argentina. - Rodriguez de la Vega, Lía; Obrador, Emanuel; Vallejos Zacarías, Nicolás (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
Towards the beginning of the 20th centuries, Argentina, until then a country influenced by European Orientalist perspectives, experienced the development of a more positive view of the East in general, and of India in particular. This phenomenon, which Bergel (2015) calls "inverted Orientalism," reflected the confluence of various elements. Within this framework, this work from a qualitative perspective, examines the figure of Ricardo Güiraldes, a prominent Argentine author of gaucho literature, who is particularly associated with India.